Implementation Of Microservices Architecture For Internship Data Recapitulation Using The Laravel Framework And The Waterfall Method At The West Java Provincial Legislative Council - Gina Purnama Insany; Rio Luigi Del Niery (Jurnal Pengabdian Masyarakat: Bisnis dan Iptek (JPMBISTEK), 2026)
The management of internship participant data in government institutions often faces administrative challenges, such as manual data compilation processes. This study aims to develop an internship data compilation application at the Regional People’s Representative Council (DPRD) of West Java Province to enhance the efficiency and accuracy of data management. The system was developed using the Laravel framework with a microservices architecture approach to ensure scalability and ease of maintenance. The Waterfall method was employed, encompassing requirements  analysis,  design,  coding,  and  testing  phases.  The  results show that the implementation of microservices architecture through RESTful API successfully integrates internship data in a centralized manner, enabling administrative staff to monitor and generate reports in real time.